Effect of substrate and strain on the mortality rate of the early larval stage of black soldier fly (Hermetia illucens) / Ramadhani Eka Putra, Nadia Fairuz Aprilia and Ida Kinasih - Putra, Ramadhani Eka; Aprilia, Nadia Fairuz; Kinasih, Ida (UiTM Press, 2022)
Black Soldier Fly (BSF) larvae (Hermetia illucens (L., 1758)) is recently applied as a bioconversion agent to manage organic wastes. However, one major limiting factor to the application on a large scale is the high mortality rate of young larvae. Studies showed that the genetic makeup and nutrition could influence the mortality rate of insect larvae. In this study, the effect of strains and substrate on the mortality rate of the early larval stage of BSF was observed. Black soldier fly eggs originated from 4 locations in Indonesia (Bogor, Ciamis, Sidoarjo, and laboratory colony). They were kept on the five substrates (fish fed, fish mill, tofu dreg, fruit, and vegetables). The total number of larvae after seven days of feeding treatment was observed. This study showed that the BSFL group fed with vegetables had the lowest survival rate (2.6 %) while the highest was found for fish feed (12.5 %). On the other hand, larva hatched from Ciamis and Sidoarjo showed the lowest survival rate (less than 5 %) while Bogor showed the highest (more than 13 %). A production system using more nutrition balance and environmentally suitable strains could lower early larva stage mortality, which improves the economic viability of BSFL production.